Comparative Analysis of two Methods of Measuring Antiretroviral Therapy Adherence in HIV-Infected Omani Patients - Gaifer, Zied (J Int Assoc Provid AIDS Care, 2019)
BACKGROUND: Antiretroviral therapy (ART) adherence is crucial to achieve HIV suppression and to prolong survival of HIV-infected patients. Although monitoring of ART adherence is standard of HIV care, there is yet no optimal method to measure ART adherence. Therefore, it is essential to compare the effectiveness of different adherence measurement tools to predict HIV suppression. METHODS: In this study, we measured ART adherence using pharmacy refill prescription and self-reported adherence questionnaire. Both the methods were compared for predicting HIV suppression in adult Omani HIV-infected patients attending the outpatient clinics at Sultan Qaboos University Hospital. RESULTS: A total of 141 HIV-infected patients were included. The pharmacy refill–based measure showed a median adherence rate of 98.90% (interquartile range [IQR]: 86%-99.45%). The self-report adherence questionnaire revealed a median adherence rate of 100% (IQR: 75-100). A significant positive correlation was found between the adherence rates measured by the 2 methods (r = 0.32, P = .01). The pharmacy refill and self-report questionnaire adherence measures were both negatively correlated with plasma HIV RNA levels (r = −0.20, P = .01 and r = −0.26, P = .04, respectively). CONCLUSION: Collectively, these findings suggest that pharmacy refill measure could serve as a valid and practical tool of ART adherence in routine clinical practice.